How Scientific Learning Shapes Creativity and Academic Achievement in Secondary Economic Education - Rahmawati Rahmawati; Sajida Taher (Economic Education Analysis Journal, 2026)
This study examines how a scientific learning approach enhances student creativity and academic achievement in economic education within the Economic Education Program at Universitas Lampung. Moving beyond conventional outcome-focused classroom action research, it employs a reflective cyclical design across three instructional cycles to capture pedagogical transformation through planning, enactment, observation, and critical reflection. Data from learning engagement, academic performance, and student creative outputs reveal a consistent improvement in conceptual mastery, participation, and product originality. The findings demonstrate that structured inquiry and iterative feedback—rather than mere procedural repetition—function as key mechanisms enabling active knowledge construction and higher-order thinking. The study’s novelty lies in conceptualizing scientific learning as an adaptive-reflective pedagogical system and providing context-sensitive evidence from economic education in the Global South, a setting underrepresented in prior research. Practically, the results suggest integrating inquiry-based cycles, reflective assessment, and creativity-oriented tasks into curriculum design, while strengthening teacher education through training in adaptive pedagogy, feedback literacy, and reflective instructional practice to improve learning quality and student creative capacity.